DIGITAL TECHNOLOGIES AS SUPPORT TO HEALTHCARE SYSTEMS IN PROMOTION OF HEALTH AND PREVENTION OF DISEASE: RAISING AWARENESS AS AN AIM OF COMMUNICATIONS - Prodović Milojković, Biljana; Sinanović, Šćepan; Prodović, Tanja; Milovanović, Olivera; Kilibarda, Tatjana; Sretenović, Ivana; Potić, Srećko; Sekulić, Jelena; Bubanj, Saša; Subotić Krivokapić, Jelena (Acta medicae Medianae, 2024)
The paper analyzes the approach to one very important phenomenon in the modern environment, which is defined as digital transformation in the healthcare system. The increasing influx of digital technologies into business processes leads to the point where the provision of healthcare services can no longer be viewed only in traditional frameworks, but it is necessary to look at the unlimited options of digital technologies, digital content and digital communications in the provision of healthcare services.The needs of the healthcare system and certain changes resulting from the development of communication and information technologies such as the Internet, social networks, mobile applications, etc. require organized work on the implementation of a strategy for new ways of doing business in healthcare. Health information and early screening awareness of oncological diseases increase the motivation for active participation of people in the implementation of preventive measures, treatments and rehabilitation.
Keywords: digital communication, social networks, e-health, m-health, oncological diseases